Association of IRGM (rs1000113 C/T) Genetic Polymorphism with the Incidence of Acute Rejection in Iranian Liver Transplanted Patients - Zahra Malekpour; Farshid Kafilzadeh (Fasa University of Medical Sciences, 2019)
Background & Objective: Autophagy has been shown to be involved in organ transplantation. IRGM (human immunity-related GTPase) has a crucial role in autophagy complex activation and ROS and microorganism elimination during graft rejection. We examined the association between rs1000113 C/T genetic polymorphism of IRGM and the risk of liver rejection in liver transplanted patients. Materials & Methods: The present study included 100 healthy people and 100 patients with liver disease that led to liver transplantation. Fifty patients were diagnosed with histologically proven acute liver rejection and the other 50 without any rejection. Both groups were matched for sex and age. To determine variants of rs1000113 C/T genetic polymorphism of IRGM, polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used. Results: A significant association was observed between liver rejection and rs1000113 C/T genetic polymorphism of IRGM (TC: p-value=0.0098, OR=2.93 CI=1.2-7.22) and (CC: p-value=0.0098, OR=0.34 CI=0.138 -0.83). Also, a significant association was observed between this polymorphism and allelic frequency in liver rejection patients. (T: p-value=0.027, OR=2.14 CI=1.027-4.57) and (C: p-value= 0.027, OR=0.46 CI=0.218 -0.97). No significant difference was found in rs1000113 C/T genetic polymorphism of IRGM, sex, blood group, and underlying disease among the healthy groups and liver transplanted patients. Conclusions: The data suggest that the rs1000113 C/T genetic polymorphism of IRGM, an autophagy-related polymorphic locus, influences liver rejection in liver transplanted patients, with the possible involvement of autophagy in transplantation. Recipients with TC genotype for IRGM are more likely to develop liver rejection compared to those with CC genotype.